Inhibition of S100A8/A9 ameliorates neuroinflammation by blocking NET formation following traumatic brain injury - Guihong Shi; Yiyao Cao; Jianye Xu; Bo Chen; Xu Zhang; Yanlin Zhu; Liang Liu; Xilei Liu; Luyuan Zhang; Yuan Zhou; Shenghui Li; Guili Yang; et al. (Redox Biology)
Traumatic brain injury (TBI) triggers a robust inflammatory response that is closely linked to worsened clinical outcomes. S100A8/A9, also known as calprotectin or myeloid-related protein-8/14 (MRP8/14), is an alarmin primarily secreted by activated neutrophils with potent pro-inflammatory property. In this study, we explored the roles of S100A8/A9 in modulating neuroinflammation and influencing TBI outcomes, delving into the underlying mechanisms. S100A8/A9-enriched neutrophils were present in the injured brain tissue of TBI patients, and elevated plasma levels of S100A8/A9 were correlated with poorer neurological function. Furthermore, using a TBI mouse model, we demonstrated that treatment with the selective S100A8/A9 inhibitor Paquinimod significantly mitigated neuroinflammation and neuronal death, thereby improving the prognosis of TBI mice. Mechanistically, we found that S100A8/A9, in conjunction with neutrophil activation and infiltration into the brain, enhances reactive oxygen species (ROS) production within neutrophils, accelerating PAD4-mediated neutrophil extracellular trap (NET) formation, which in turn exacerbates neuroinflammation. These findings suggest that S100A8/A9 amplifies neuroinflammatory responses by promoting NET formation in neutrophils. Inhibition of S100A8/A9 effectively attenuated NET-mediated neuroinflammation; however, when PAD4 was overexpressed in the brain using adenovirus, leading to an increased formation of NET in the brain, the anti-inflammatory effects of S100A8/A9 inhibition were markedly diminished. Further experiments with PAD4 knockout mice confirmed that the reduction of NETs could substantially alleviate S100A8/A9-driven neuroinflammation. Finally, we established that the suppression of NET formation by S100A8/A9 inhibition is primarily mediated through the AMPK/Nrf2/HO-1 signaling pathway. These findings underscore the critical pathological role of S100A8/A9 in TBI and emphasize the need for further exploration of S100A8/A9 inhibitor Paquinimod as a potential therapeutic strategy for TBI.